Product Advantage, Customer Relationship Marketing, and Service Quality on Customer Satisfaction of Bank Syariah Mandiri in Surabaya - Panjaitan, Hotman; Djunaedi, Djunaedi (International Review of Management and Marketing, 2017)
This paper discusses the causal relationship between product advantages, customer relationship marketing, service quality, and customer satisfaction of Bank Syariah Mandiri in Surabaya. The population in this study is a customer savings Bank Syariah Mandiri, which is in 3 branches offices and 15 sub-branches in Surabaya. From the test results in the model in this study, with Generalized Least Square Estimation, structural equation model analysis, convenience sampling method and Amos 22 software aid, on 300 respondents. The results showed that the product advantage affects on customer satisfaction. Customer relationship marketing affects on service quality. Customer relationship marketing affects customer satisfaction. service quality affects customer satisfaction. Research shows customer relationship marketing dominant influence on consumer satisfaction. Suggested for bank management should pay attention to the product owned considering the role of product superiority to customer satisfaction. Keywords: product advantage, customer relationship marketing, service quality, customer satisfaction JEL Classifications: L15, M31